EFL Undergraduate Students' Perceptions of Slick Write as Web-Based Writing Support Tools: A Qualitative Case Study - Anis Syafa Wani; Utami Dewi (Universitas Islam Negeri Palopo, 2025)
The integration of web-based writing support tools in EFL writing instruction has gained attention due to their potential to address students' writing challenges. This study investigates EFL undergraduate students' perceptions of Slick Write as a web-based writing support tool in academic contexts. The study employed a qualitative case study approach. At the same time, the data were collected from ten eighth-semester undergraduate students at the State Islamic University of North Sumatra through closed-ended questionnaires and semi-structured interviews. All participants had prior experience using Slick Write for at least one semester in their academic writing tasks. Data from questionnaires and interviews were analyzed using Braun and Clarke's six-step thematic analysis framework. The findings revealed five main themes: effectiveness in detecting grammar errors, clarity and quality of feedback, increased writing autonomy and confidence, enhanced structured revision practices, and suitability with academic writing conventions. A significant concern identified was potential over-reliance on automated tools. While findings highlight Slick Write's benefits in supporting academic writing development, they also suggest the need for balanced implementation to prevent dependency. This study contributes to computer-assisted language learning literature by examining a less-explored tool through sociocultural and automated writing evaluation theoretical lenses, providing insights into technology-mediated writing instruction in Indonesian Islamic higher education contexts. Future research should explore the long-term impact of web-based writing tools on writing development and investigate their effectiveness across different academic disciplines